MACHINE TRANSLATION METHODS AND SOME CURRENT TRENDS - Шевченко, Ольга (SWorldJournal, 2023)
This paper provides an overview of some major machine translation methods designed to speed up the rate of multilingual text translation. Machine translation is achieved by computer software transforming text from one language to another. At present, d